Numerical investigation of a novel micro combustor with a central and bilateral slotted blunt body. (1st July 2021) - He, Ziqiang; Yan, Yunfei; Fang, Ruiming; Ou, Zhiliang; Zhang, Zhonghui; Yang, Zhongqing; Zhang, Zhien
Abstract: To improve the combustion stability at micro scale, the micro combustor with a central and bilateral slotted blunt body (MCSB) exhibiting significant combustion performance improvement is designed. The new one can not only effectively prevent the flame tip opening, but also exhibit higher combustion efficiency and blown-off limit. Its blown-off limit can reach 756 cm 3 /s at the flow rate ratio of 0.2 and the bluff body angle of 90°, which is 61.5% higher than that of the conventional one with the blown-off limit of 468 cm 3 /s. The combustion efficiency improves with the growth of the flow rate ratio, while the blown-off limit of MCSB increases first and then decreases. The blown-off limit of MCSB with the bluff body angle of 90° reaches to the peak value of 792 cm 3 /s at the flow rate ratio of 0.15. Moreover, the increase of the bluff body angle provides better combustion efficiency and stability. Highlights: Proposed a novel micro combustor with a central and bilateral slotted bluff body. Studied the influence of flow rate ratio on combustion performance. Investigated the effect of bluff body angle on combustion characteristics.